Those of my blood : constructing noble families in medieval Francia - Bouchard, Constance Brittain (Middle Ages series., 2001)
"Focusing on the Frankish realm between the eighth and twelfth centuries, Constance Brittain Bouchard outlines the operative definitions of "family" in this period when there existed various and flexible ways by which individuals were or were not incorporated into the family group. Even in medieval patriarchal society, women of the aristocracy, considered outsiders by their husbands and their husbands' siblings and elders, were never completely marginalized; paradoxically they represented the very essence of "family" to their male children. Bouchard also engages in the ongoing scholarly debate about the nobility around the year 1000, arguing that there was no clear point of transition from amorphous family units to agnatically structured kindred. Instead, she points out that great noble families always privileged the male line of descent, even if most did not establish father-son inheritance until the eleventh or twelfth century. Those of My Blood clarifies the complex meanings of medieval family structure and family consciousness and shows the many ways negotiations of power within the noble family can help explain early medieval politics."--Jacket